STUDI PEMECAHAN PENYULANG OMBILIN UNTUK PERBAIKAN DROP TEGANGAN DI PT PLN (PERSERO) RAYON PADANG PANJANG MENGGUNAKAN APLIKASI ETAP - Dasman Dasman (Ensiklopedia of Journal, 2022)
Ombilin feeder is one of the longest feeders in PT. PLN (Persero) Rayon Padang Panjang. The total length of the medium voltage network is 117.116 Kms. With a large load, the length of the network and the cross-sectional area vary, causing a voltage drop in the feeder. According to SPLN 72:1987 the allowable voltage drop is 5%. Therefore, a solution is needed to reduce the voltage drop on the feeder to comply with PLN standards. One of them is by changing the load splitting. The loading pattern was changed by optimizing the cross-sectional area of the 240 mm2 AAAC wire which has a better KHA and a smaller impedance. To analyze and find out how much improvement the voltage drop is before and after the load splitting is done, a simulation is carried out using the ETAP 12.6 software. Based on the simulation results, the voltage drop before breaking the load in Baing is 6.67% with a voltage value of 19.413 KV and in Simawang data it is 6.71% with a terminal voltage value of 19.404 kV. After breaking the load, the voltage drop in Baing is 4.19% with a voltage value of 19.929 KV and in Data Simawang it is 4.23% with a terminal voltage value of 19.921 kV. Based on these results, the cause of the voltage drop is influenced by several things, namely the current flowing in the channel, the distance and cross-sectional area of the conductor used.Keywords: Load, Voltage Drop, ETAP.